Design of new glycosyl–O‐fipronil conjugates with improved hydrolysis efficiency assisted by molecular simulations. Issue 6 (24th April 2022) - Wang, Bingfeng; Yang, Chen; Jiang, Xunyuan; Wen, Yingjie; Tian, Yongqing; Zhao, Chen; Xu, Hanhong
Abstract: BACKGROUND: In a previous study, we showed that two glycosyl–pesticide conjugates with a β ‐d ‐glucoside moiety, N‐{3‐cyano‐1‐[2, 6‐dichloro‐4‐(trifluoromethyl) phenyl]‐4‐[(trifluoromethyl)‐sulfinyl]‐1H‐pyrazol‐5‐yl}‐2‐aminoethyl‐β‐d ‐glucopyranoside (GOF) and N‐{3‐cyano‐1‐[2, 6‐dichloro‐4‐(trifluoromethyl)phenyl]‐4‐[(trifluoromethyl) sulfinyl]‐1H‐pyrazol‐5‐yl}‐1‐(2‐triazolethyl‐β‐d ‐glucopyranoside)‐1H‐1, 2, 3‐triazole‐4‐methanamine (GOTF), can move in the phloem and be hydrolyzed by β ‐glucosidase at different rates. Simulations were carried out to investigate differences in the hydrolysis process in GOF, GOTF and p ‐nitrophenyl β ‐d ‐glucopyranoside ( p NPG). A new series of glycosyl– O ‐fipronil conjugates was then designed and synthesized based on the simulation results. The phloem mobilities of the new conjugates were examined using a Ricinus model, and their hydrolysis efficiencies based on β ‐glucosidase were determined. RESULTS: New glycosyl– O ‐fipronil conjugates GOE2–6 were designed and synthesized. To reduce steric hindrance, the conjugating site of the glycone moiety was moved to the 4′‐sulfonyl group on the pyrrole ring. As a result, the hydrolysis efficiencies of the new conjugates were significantly improved, with GOE4 having the highest hydrolysis efficiency. All five conjugates could be transported in Ricinus phloem sap, consistent with previously studied glycosyl– O ‐fipronil conjugates. The insecticidal activities of the conjugates were tested against Plutella xylostella . CONCLUSION: A strategy for the development of new phloem‐mobile pesticides was proposed: linking a glycosyl group to the existing pesticide structure with a linear alkyl connection approximately four carbons in length. The resultant conjugates feature not only good phloem mobility, but also potential high bioactivity due to the efficient release of active pesticide components under the action of glucosidase. © 2022 Society of Chemical Industry. Abstract : New glycosyl– O ‐fipronil conjugates were designed based on an analysis of existing structures using molecular dynamic methods, and possessed enhanced hydrolysis efficiencies and phloem mobilities. These molecules have the potential to release active substances under the assistance of β ‐glucosidase and promote the chemical defense of plants against insects.